The Choice of Anesthetic Drugs in Outpatient Hysteroscopic Surgery: A Systematic Review and Network Meta-Analysis. (21st September 2022) - Li, Shengnan; Wu, Bin; Peng, Bibo; Zhang, Qian; Zhao, Hongdan; Hou, Kun; An, Lina
Abstract : Objective . Hysteroscopy is a minimally invasive gynecologic technique that is widely practiced in outpatient procedures. The choice of anesthesia is a key factor for the surgical outcome and postoperative recovery. This study was conducted to assess the effects of different anesthetic modalities based on dexmedetomidine in outpatient hysteroscopic surgery anesthesia. Methods . We did a systematic review and network meta-analysis of outpatient hysteroscopic surgery anesthesia. We searched Pubmed, Embase, and Cochrane-Library from database inception to December 31, 2021. Duplicate literature was excluded and screened separately for initial screening at three tiers: article title, abstract, and full text before deciding whether to include in this study against the above criteria. Results after analysis of categorical variables were expressed as ORR Ratio (95% CI) and continuous variables were expressed as Mean Difference (95% CI). Data collation and analyses were performed using the gemtc package in the R language. Results . Four trials were finally included with data for 301 participants, three anesthetic drugs, and five anesthetic modalities. A fixed-effects model was used for the different anesthesia modalities without significant heterogeneity (all I2<20%) in the analysis of adverse events (AEs), the incidence of respiratory depression, operative time, and time in the post-anesthesia care unit (PACU). Remimazolam tosylate was associated with a lower incidence of AEs versus dexmedetomidine, and significant differences between dexmedetomidine and propofol were absent. Propofol and various doses of remimazolam tosylate resulted in a lower incidence of respiratory depression versus dexmedetomidine, with an absence of differences between propofol and dexmedetomidine. The operative time for different anesthetic modalities was, in descending order, dexmedetomidine < remimazolam tosylate (0.60 mg/kg/h <0.48 mg/kg/h) < propofol < remimazolam tosylate (1.00 mg/kg/h), despite the absence of intergroup differences. Propofol was associated with a longer time in PACU versus dexmedetomidine and remimazolam tosylate (1.00 mg/kg/h); those of dexmedetomidine and remimazolam tosylate (1.00 mg/kg/h) were similar. The time in PACU for different anesthetic modalities, in descending order, was dexmedetomidine < remimazolam tosylate (1.00 mg/kg/h) < propofol. Propofol was associated with a longer time in PACU versus dexmedetomidine and remimazolam tosylate. Conclusion . In outpatient hysteroscopic surgery anesthesia, dexmedetomidine was associated with a higher incidence of AEs and respiratory depression and a shorter operative time and time in PACU versus remimazolam tosylate and propofol. Remimazolam tosylate showed safety benefits with a similar duration of PACU stay versus dexmedetomidine. Therefore, the choice of anesthetic drugs in outpatient surgery requires consideration of the patient's conditions and preferences.